Analytical investigation of the armature current influence on the torque and radial force in eccentric consequent‐pole PM machines - Samad Taghipour Boroujeni; Seyed Payam Emami; Noureddine Takorabet; Amin Mahmoudi (IET Electric Power Applications, 2021)
Abstract In this work, the electromagnetic torque and the unbalanced magnetic force (UMF) in eccentric consequent pole PM (CPPM) machines are investigated. For this investigation, in the first part of the paper, an exact analytical model is provided for the CPPM machine by solving the Poisson equation in the eccentric and salient air gap. In the analytical modelling process, the concept of equivalent magnetizing current (EMC), the subdomain technique, and a bilinear transformation are applied. The obtained model is verified by means of FEA. In the second part of the paper, by using the developed model, the relationship between the machine electromagnetic torque and the UMF to the d‐ and q‐axis components of the armature current is studied. It is shown that in CPPM machines, the influence of the q‐axis current on the electromagnetic torque is much higher than the effect of the d‐axis current. On the other hand, the eccentric machine UMF is strongly dependent on the d‐axis armature current while the variation of the UMF due to the changes in the q‐axis current is small. Therefore, in eccentric CPPM machines, UMF could be suppressed by injecting a negative d‐axis armature current (flux weakening).